1989
DOI: 10.1246/cl.1989.909
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and Distribution of the Carbazole Unit in Monolayers and Their Fluorescence Characteristics

Abstract: Double-chain ammonium amphiphiles that contain the carbazole ring formed stable monolayers on water. Their fluorescence patterns indicated different packing modes of the chromophore which depended on chemical structure and component distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…It has been reported that the isotherm of DDOAB is sensitive to experimental conditions and, in particular, the concentration and type of counterion . A comparison of the isotherm of DDOAB on pure water given in Figure with others reported in the literature ,, reveals good agreement. Although there is some difference between the isotherm presented here and that of Marra, this may be understood by the different electrolyte concentration and spreading solvent.
3 Surface pressure−area isotherms of DDOAB on water and polyion solution subphases at various pH values.
…”
Section: Resultssupporting
confidence: 68%
“…It has been reported that the isotherm of DDOAB is sensitive to experimental conditions and, in particular, the concentration and type of counterion . A comparison of the isotherm of DDOAB on pure water given in Figure with others reported in the literature ,, reveals good agreement. Although there is some difference between the isotherm presented here and that of Marra, this may be understood by the different electrolyte concentration and spreading solvent.
3 Surface pressure−area isotherms of DDOAB on water and polyion solution subphases at various pH values.
…”
Section: Resultssupporting
confidence: 68%